The State of Public Health Education and Science During and After the Fall of the Soviet Union: Achievements, Remaining Challenges, and Future Priorities - Gotsadze, George; Mirzikashvili, Nino; Kekelidze, Dali; Kalandarishvili, Sopio; Kalandadze, Iagor; Abiatari, Ivane; Zoidze, Akaki (Frontiers in Public Health, 2022)
Objectives In the post–COVID-19 world, when the adequacy of public health workforce education is being critically re-evaluated, this study undertakes a historical analysis of how the educational and scientific field of public health developed during and after the fall of the Soviet Union in 1991. The study intends to historically contextualize public health education and science development in former Soviet Republics. It attempts to document achievements after gaining independence and identify remaining challenges that need to be addressed for advancing public health science and education in Former Soviet Union countries to better prepare them for future pandemics and address current health challenges of the nations. Methods The study used a mixed-methods review approach combining both a literature review, information collection from the school's websites, and secondary analysis of the quantitative data available about scientific outputs—peer-reviewed articles. Results During communist rule and after the fall of the Soviet Union, the main historical events seem to have shaped the public health field of former Soviet countries, which also determined its eventual evolution. The international efforts post-1991 were instrumental in shifting medically oriented conceptualization of public health toward Western approaches, albeit with variable progress. Also, while scientific output has been growing from 1996 to 2019, sub-regional differences remain prominent. Conclusion The region seems to have matured enough that it might be time to start and facilitate regional cooperation of public health schools to advance the field of public health and research. Regional and country variabilities feature prominently in the volume and quality of scientific output and call for the immediate attention of national governments and international partners.